The influence of product quality and Word of Mouth (WOM) on repurchase intentions through the mediation of consumer satisfaction - Sartika, Ipen; Salim, Muhartini (Universitas Wiralodra, 2024)
Repurchase intention is one of the main goals of the marketing strategy planned by every businessperson. This research aims to determine the direct influence of product quality and word of mouth on repurchase intentions, which is mediated by consumer satisfaction with Mixue products in Bengkulu City, which occurs due to the phenomenon of the Mixue brand, which is starting to mushroom in every region of Indonesia. The research method uses a quantitative approach, with a sample of 100 respondents using a purposive sampling. Data is processed using SmartPLS 4. The research results show that product quality and word of mouth have a significant effect on consumer satisfaction, consumer satisfaction has a significant effect on repurchase intention, product quality has no significant effect on repurchase intention, word of mouth has a significant effect on repurchase intention, product quality and word of mouth has a significant effect on repurchase intention through consumer satisfaction. This research provides insight for companies to increase consumers repurchase intentions by recognizing the positive impact of product quality and word of mouth in helping companies achieve customer loyalty and sustainable business growth.